Abdominoscrotal lymphangioma treated with bleomycin sclerotherapy: A case report - Hien Duy Pham; Duy Le Dinh Tran; Thom Hoang Dang; Son Hoang Nguyen; Vy Huynh Khanh Nguyen; Quang Thanh Nguyen (Elsevier, 2024)
Introduction: Lymphatic malformations (LMs) or lymphangiomas are rare congenital anomalies affecting the lymphatic system. They are predominantly found in the head and neck, with less common occurrences in abdominal cavity or scrotum. Bleomycin is among the sclerotic agents used, capable of inducing a non-specific inflammatory process leading to thrombosis and fibrosis of the cyst. However, there is limited literature regarding the efficacy of Bleomycin as a standalone treatment for large and mixed types of cystic LMs. Case presentation: A 17-year-old male presented with swelling in the right inguinal and scrotal regions, without tenderness. Ultrasound and contrast-enhanced computed tomography scan (CT scan) revealed a large, well-defined multiloculated cystic lesion measuring 7x8x8cm in the pelvic region, extending into the left inguinoscrotal region (15x6x8cm), consistent with LMs. Treatment comprised aspiration of cystic fluid followed by Bleomycin injection, administered at a maximum dosage of 0.5 IU/kg body weight under general anesthesia. A sequence of five sclerotherapy sessions of Bleomycin injections was carried out, with each session spaced one month apart. Following 15 months of observation, no intra-abdominal cystic masses were identified, and scrotal ultrasound displayed near-complete resolution. Only a fibrotic tissue measuring 1.5 × 1cm in size was identified in the scrotum, and it remained stable across three consecutive scans, indicating that no further intervention was required. Conclusion: Based on this case study, sclerotherapy using intralesional Bleomycin injection for large, complex LMs in children appears to be safe and effective. This scarless approach seems to provide good cosmetic outcomes and poses a minimal risk of neurovascular injury.